How Can Education Managers In Secondary Rural Schools Generate Funds Within A School-Based Management Framework? - Ngwenya, V.C.; Sibanda, D. (Advances in Social Sciences Research Journal, 2017)
This paper reports on how education managers in rural secondary schools may generate funds informed by the school-based management framework as financial management in Zimbabwean schools has been decentralised to school level. Looking at the school system on a continuum, on one end there are first class schools which have well developed infrastructure and are well resourced. On the other extreme, there are dilapidated and scantly resourced ones. However, within this scenario, there are some affluent rural schools depending on the responsible authority which can compete comparatively with their urban counterparts. This paper focuses on the critical role of the educational manager in resource mobilisation assisted by willing internal and external stakeholders, philanthropic foundations included. Since the bulk of the parents are peasant farmers, who rely on rain-fed agriculture, education managers are advised to link up with the external community for additional funding if human capital, so much needed by both the education sector and corporate world is to be developed. The study employed a qualitative approach of a case study design involving semi-structured face-to-fact interviews with purposefully selected participants comprising an education manager and four teachers. A small sample was considered ideal for an in-depth study of the phenomenon. Data collected was triangulated and verified with the participants for accuracy and credibility. The findings suggested that the volatile economic environment education managers operate in points towards soliciting funds from external stakeholders as part of their turnaround strategies. Armed with the appropriate strategic plan a rural school may resemble an oasis in the desert. We conclude that schools in impoverished environments should look elsewhere for funding. Equally important is the fact that as researchers, we are conscious of the fact that our cross-sectional study is based on qualitative data which may limit the generalisation of such findings to a different context. Key words: Accountability, Foundation Board, Reporting structure, School Finance Policy, Finance Sub-Committee, Stakeholders.